Dredging of lake and application of sapropel for improvement of light soil properties - Bakšienė, Eugenija; Ciūnys, Antanas (Journal of Environmental Engineering and Landscape Management, 2012)
Approx. 1.5 billion m3 of sapropel are accumulated in silty Lithuanian lakes. Sapropel is a valuable organic and limy matter, which can be used for fertilisation and soil improvement. Silted lakes usually require mechanical cleaning, i.e. removal of lake sapropel. Such cleaning was carried out in one of the lakes of Lithuanian – Lake Ilgutis: using a dredge, sapropel was extracted, dried in sediment bowls to 80–85% of humidity, carried to a field and insert into the soil. Summarised results of the long-term experiment showed that calcareous sapropel can reduce soil acidity and increase the amount of exchangeable bases (Ca+Mg). Under the influence of sapropel, the contents of organic carbon and total nitrogen increased as well. The results of investigations demonstrated that by the end of the second (after 12 years), third (after 18 years) and fourth (after 24 years) rotation, the effect of sapropel on soil chemical properties was positive. Compared with limestone, calcareous sapropel improved physical characteristics of the soil to a greater extent. Article in English. Ežero valymas ir sapropelio naudojimas dirvožemio savybėms gerinti Santrauka. Uždumblėjusiuose Lietuvos ežeruose susikaupę apie 1,5 mlrd. m3 sapropelio. Sapropelis, vertinga biogeninė organinė ar kalkinė medžiaga, gali būti plačiai naudojamas dirvoms tręšti ir gerinti. Ežerai, kasant sapropelį iš jų, būtų išvalomi ir pagilinami. Tai padėtų atkurti jų būklę, funkcinę paskirtį. Žemsiurbe MZ-8 buvo kasamas sapropelis iš Ilgučio ežero ir sėsdintuvuose džiovinamas, tada išvežamas į laukus, ir tręšiama dirva. Nustatyta, kad dirvožemio agrocheminės savybės kas rotacija prastėjo, tačiau nepasiekė rodiklių, buvusių prieš bandymų rengimą. Teigiamas sapropelio veikimas pastebėta po antrosios (12 metų), trečiosios (18 metų) ir ketvirtosios (24 metų) sėjomainų rotacijų. Sapropelis laukams tręšti turėjo teigiamos įtakos dirvožemio fizikinėms savybėms. Kalkinis sapropepelis veikė geriau nei klintmilčiai. Reikšminiai žodžiai: žemsiurbė, sapropelis, transportavimas, dirvožemis, cheminės savybės, fizikinės savybės